تعیین ربا کا درست منہج اور سود کے جواز کے دلائل کا تجزیہ (Al-Qamar, 2022)
Defining Ribā has proved to be a difficult task for scholars in the contemporary world. The present paper argues that the problem lies the flawed methodology of these scholars. Hence, the paper focuses on the methodology of the Muslim jurists who held that Ribā was a technical term (Mujmal) the meaning of which was elaborated by the Prophetic traditions about ribā. Hence, believing in the inseparability of the Qur’an and the Sunnah, the jurists connected the Qur’anic verses and the Prophetic traditions about Ribā and defined Ribā as: excess without a counter-value stipulated in a contract of exchange of property. The paper argues that this definition of Ribā answers all significant questions about the term, such as: whether bank-interest is included in the scope of Ribā; whether the prohibition of Ribā covers interest on credit raised for commercial purposes; whether paying interest is a lesser sin than receiving interest; whether indexation of loans is permitted in Islam; whether charging a higher price in credit-sale is permitted; whether Islamic law recognizes the concept of time-value of money; and so on. After answering these questions, the paper also examines some of the important arguments forwarded by various economists for justifying interest and concludes that these arguments do not carry any weight.
Keywords: Ribā; mujmal; interest; credit-sale; indexation